2012
DOI: 10.1155/2012/874076
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Study and Demonstration of an Aluminum and Ice Solid Propellant

Abstract: Aluminum-water reactions have been proposed and studied for several decades for underwater propulsion systems and applications requiring hydrogen generation. Aluminum and water have also been proposed as a frozen propellant, and there have been proposals for other refrigerated propellants that could be mixed, frozen in situ, and used as solid propellants. However, little work has been done to determine the feasibility of these concepts. With the recent availability of nanoscale aluminum, a simple binary formul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…The experimental research [5] shows that the burning time of an aluminum particle in water vapor is determined by its initial diameter was considered as the only coefficient used for fitting the computed results and experimental data. The coefficient was reconciled by comparing the calculated burning rate of a frozen nano-aluminum-water suspension (ALICE fuel) with experimental data [7]. The calculation results of the burning rate for the same suspension depending on pressure are presented in [2].…”
Section: Construction Of the Mathematical Modelmentioning
confidence: 99%
“…The experimental research [5] shows that the burning time of an aluminum particle in water vapor is determined by its initial diameter was considered as the only coefficient used for fitting the computed results and experimental data. The coefficient was reconciled by comparing the calculated burning rate of a frozen nano-aluminum-water suspension (ALICE fuel) with experimental data [7]. The calculation results of the burning rate for the same suspension depending on pressure are presented in [2].…”
Section: Construction Of the Mathematical Modelmentioning
confidence: 99%
“…The system is explained in more detail in previous reports. [25][26][27][28][29] Previously, we reported that RAM is estimated to repeatedly throw the powder upward into the air and perform mixing by utilizing free fall (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies have been conducted to characterize the combustion of aluminum particles at nano-and micro-scales with water [9][10][11][12][13]. Also, several numerical and analytical models have been developed to get a better understanding of this process [14][15][16].…”
Section: Introductionmentioning
confidence: 99%